2015
DOI: 10.1111/tmi.12549
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of community‐based, self‐collected HPV testing vs. visual inspection with acetic acid for cervical cancer screening in Kampala, Uganda: preliminary results of a randomised controlled trial

Abstract: Abstractobjectives To compare two cervical cancer screening methods: community-based self-collection of high-risk human papillomavirus (HR-HPV) testing and visual inspection with acetic acid (VIA).methods Pilot randomised controlled trial of 500 women aged 30-65 in the community of Kisenyi, Uganda. Women randomised to self-collection-based HR-HPV testing provided a cervico-vaginal swab for HR-HPV, and results were provided by phone after laboratory testing. Women who tested HPV positive were referred for VIA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 15 publications
8
112
0
Order By: Relevance
“…This is much higher than other studies that ASPIRE has conducted in Kisenyi where HPV positivity rates among HIV negative women was only 28.9%, of which 5.3% were HPV 16 or 18 [22]. Our HIV positive population was more likely to live or work outside of Kisenyi, compared to past studies where self-collection was offered by community outreach workers at their homes [23, 24]. This suggests that a model for screening with self-collection for WHIV may be more appropriately based out of a health center, as these women are already engaged in care, thereby avoiding unnecessary travel.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is much higher than other studies that ASPIRE has conducted in Kisenyi where HPV positivity rates among HIV negative women was only 28.9%, of which 5.3% were HPV 16 or 18 [22]. Our HIV positive population was more likely to live or work outside of Kisenyi, compared to past studies where self-collection was offered by community outreach workers at their homes [23, 24]. This suggests that a model for screening with self-collection for WHIV may be more appropriately based out of a health center, as these women are already engaged in care, thereby avoiding unnecessary travel.…”
Section: Discussionmentioning
confidence: 68%
“…Unlike the present study where many women were asked to attend self-collection outside of their normal HIV appointment schedule; had screening been integrated with routine HIV care, uptake and follow-up would have undoubtedly been higher. Uptake of self-collection based screening in Kisenyi was 99% in a recent study [24], and a subgroup analysis demonstrated 95% uptake among WHIV [22]. Similarly, we believe that the distance to the tertiary care hospital where colposcopy is conducted, as well as the time required for the additional visit were barriers to follow up assessment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Expanding screening coverage to rural areas— where the vast majority of the population resides— will be logistically challenging, but HPV self‐collection facilitated by community health workers may be feasible and may reduce the burden on the limited number of health facilities that provide screening. A recent randomized trial in an impoverished area of Kampala, Uganda that found 99% of women approached for self‐collection of HPV specimens at home or work participated, compared with 48% of women invited to attend the clinic for screening . Whether this increase in screening uptake occurs in rural settings remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐collection also means that practitioners do not need to conduct the first part of screening—collection of the specimen—and allows programs to focus scarce resources on follow‐up of women who are HPV positive. In addition, with a paradigm shift to integration of broader reproductive health issues, self‐collection for HPV testing can be coupled with testing for sexually transmitted infections, such as Chlamydia trachomatis and Neisseria gonorrhea , further expanding access to important reproductive health interventions for women …”
Section: Self‐collection Of Samplesmentioning
confidence: 99%